2016
DOI: 10.1103/physreve.94.012124
|View full text |Cite
|
Sign up to set email alerts
|

Aspiration promotes cooperation in the prisoner's dilemma game with the imitation rule

Abstract: A model of stochastic evolutionary game dynamics with finite population of size N+M was built. Among these individuals, N individuals update strategies with aspiration updating, while the other M individuals update strategies with imitation updating. In the proposed model, we obtain the expression of the mean fraction of cooperators and analyze some concrete cases. Compared with the standard imitation dynamics, there is always a positive probability to support the formation of cooperation in the system with th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
25
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(26 citation statements)
references
References 47 publications
1
25
0
Order By: Relevance
“…Moreover, Xu et al [34] demonstrated that average abundance function reaches the highest value when both interaction coefficient and aspiration level are at appropriate level. Xuesong Liu [35] affirmed that the combination of aspiration rule and imitation rule is conducive to the increasing of average abundance function. Chen et al [36] corroborated that the suboptimal selection based on aspiration level is beneficial for average abundance function.…”
Section: The Comparison Between Aspiration Rule and Imitation Rulementioning
confidence: 93%
“…Moreover, Xu et al [34] demonstrated that average abundance function reaches the highest value when both interaction coefficient and aspiration level are at appropriate level. Xuesong Liu [35] affirmed that the combination of aspiration rule and imitation rule is conducive to the increasing of average abundance function. Chen et al [36] corroborated that the suboptimal selection based on aspiration level is beneficial for average abundance function.…”
Section: The Comparison Between Aspiration Rule and Imitation Rulementioning
confidence: 93%
“…In the complex battlefield environment, the information acquisition is incomplete, asymmetric, which requires the swarm to achieve selfmanagement and self-coordination, and this requirement just coincides with the aspiration-driven dynamics. Moreover, the existing results show that, in both prisoner's dilemma game and public goods game, the dynamic mechanism driven by aspiration can improve the average abundance value and promote cooperation more than the traditional imitation dynamics [43,44].…”
Section: Mathematical Problems In Engineeringmentioning
confidence: 99%
“…Therefore, the inclusion of heterogeneous updating is much needed to reflect a more realistic scenario. In fact, some of the previous studies [39,40] have already explored the presence of heterogenous updating in classical social dilemma games, such as dyadic games. In those cases, the existence of aspiration-led updating in addition to the imitation rule has seemed to ensure the survival of cooperation, even in a defective milieu (such as the Prisoner's Dilemma; PD) [37,38].…”
Section: Introductionmentioning
confidence: 99%